Elbow Arthrodesis Surgical Technique. (August 2021) - Couso, Megan; Sherman, Nathan; Lowe, Jason
Abstract : Summary: Elbow arthrodesis is an uncommon salvage procedure indicated for failed total elbow arthroplasty, segmental bone loss near the elbow, and severe postinfectious or posttraumatic arthritis. This video demonstrates the surgical technique for elbow arthrodesis in a patient with segmental bony defect of the ulna and postinfectious and posttraumatic elbow arthritis after a severe left arm degloving injury with Monteggia fracture dislocation and radial head fracture.